Cybersecurity law - Kosseff, Jeff 1978- (Wiley, 2023)
"Cybersecurity is the process of applying security measures to ensure confidentiality, integrity, and availability of data. The goal of cybersecurity is to protect assets, which includes data, desktops, servers, buildings, and most importantly, humans"